On the dispersion strengthening mechanisms in ODS materials - Reppich, Bernd (International Journal of Materials Research, 2022)
The interaction of dislocations with finely-dispersed incoherent, non-shearable, hard particles governing the strength of oxide dispersion-strengthened (ODS) materials is briefly reviewed with particular emphasis on the basic features of the operating high-temperature mechanisms. The experimental determination of the particle-threshold stress within the yield stress- increment approach as well as its modelling in terms of the "interfacial pinning" mechanism are outlined and exemplified with the austenitic ODS superalloy MA 754 and its ferritic counterparts MA 956 and PM 2000. The available data of very recent high-voltage electron microscopic observations on MA 754 and MA 956 are re-evaluated. In situ straining experiments image moving dislocations under full stress and yield valuable quantitative informations characterizing the controlling (attractive) dislocation - dispersoid particle interaction which are not directly accessible by other methods, such as the (effective) obstacle density; the specific obstacle (particle) strength derived from the relevant interaction parameters; the locally acting shear stress estimated using the measured particle spacings, the curvature of the bowed-out dislocation segments in the stress-applied state, and their line tension calculated within the de Wit-Koehler model. The findings obtained in combination with the results of earlier conventional electron microscopy and those of critically analyzed macroscopic deformation data support convincingly our understanding of the elementary physical mechanisms underlying elevated temperature dispersion strengthening which promises, eventually, to put microstructural-based model description of the yield/creep strength on a more quantitative footing.
CRIS-Team WoS Importer:2022-01-14